2013
DOI: 10.1128/jvi.06968-11
|View full text |Cite
|
Sign up to set email alerts
|

Residues Arg283, Arg285, and Ile287 in the Nucleotide Binding Pocket of Bovine Viral Diarrhea Virus NS5B RNA Polymerase Affect Catalysis and Fidelity

Abstract: bResidues Arg283, Arg285, and Ile287 are highly conserved amino acids in bovine viral diarrhea virus RNA polymerase (BVDV RdRp) and RdRps from related positive-strand RNA viruses. This motif is an important part of the binding pocket for the nascent RNA base pair during initiation and elongation. We found that replacement of the arginines with alanines or more conserved lysines or replacement of isoleucine with alanine or valine alters the ability of the mutant RdRps to incorporate ribonucleotides efficiently.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…For example, by using different strains of FMDV, one study identified one substitution (M296I) while other independent studies identified three (P44S, P169S and M296I) or four (D5N, A38V, M194I and M296V) different substitutions that confer resistance to ribavirin and increased fidelity (Agudo et al, 2010;Sierra et al, 2007;Zeng et al, 2014). A couple of amino acid mutations were also identified in coxsackievirus B3 virus, human enterovirus 71 virus and bovine viral diarrhea virus (Curti & Jaeger, 2013;Gnädig et al, 2012;Sadeghipour et al, 2013). For the two amino acid substitutions identified in PRRSV in this study, when they were introduced into the PRRSV VR2385 infectious clone backbone, the rescued reconstituted virus vA283T showed a more ribavirin-resistant profile and fewer quasispecies variants than the other reconstituted virus vH421Y (Fig.…”
mentioning
confidence: 89%
“…For example, by using different strains of FMDV, one study identified one substitution (M296I) while other independent studies identified three (P44S, P169S and M296I) or four (D5N, A38V, M194I and M296V) different substitutions that confer resistance to ribavirin and increased fidelity (Agudo et al, 2010;Sierra et al, 2007;Zeng et al, 2014). A couple of amino acid mutations were also identified in coxsackievirus B3 virus, human enterovirus 71 virus and bovine viral diarrhea virus (Curti & Jaeger, 2013;Gnädig et al, 2012;Sadeghipour et al, 2013). For the two amino acid substitutions identified in PRRSV in this study, when they were introduced into the PRRSV VR2385 infectious clone backbone, the rescued reconstituted virus vA283T showed a more ribavirin-resistant profile and fewer quasispecies variants than the other reconstituted virus vH421Y (Fig.…”
mentioning
confidence: 89%
“…The assays we established in this work fall into the third category, which utilize either genome-derived or artificial heteropolymeric template sequences normally shorter than 100 nt. By using different NTP combinations as the primary strategy to allow the monitoring of RNA polymerization down to the single-nucleotide level, these assays offer the best power in dissecting the mechanism of RNA synthesis (19,(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that RdRPs of the family Flaviviridae carry out de novo initiation in viral genome replication. However, primer-dependent activities of these enzymes have been reported from various in vitro assays (19,33), providing valuable measures of RNA synthesis. We first established a primer-dependent assay based on what had been utilized in poliovirus (PV) polymerase systems (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that several camel single domain intrabodies targeting the HIV-1 Rev protein, the IFV nucleoprotein, and the HCV envelope protein could exert antiviral activity (Ashour et al, 2015;Boons et al, 2014;Serruys et al, 2009), indicating that intracellularly-expressed Nbs are very effective in protecting the host against viral infection. BVD is of great concern worldwide to the H. Duan, et al Veterinary Microbiology 240 (2020) 108449 bovine industry, due to its complex genetic variability and lack of effective therapeutic drugs that can be used to date (Curti and Jaeger, 2013). Whether intracellularly-expressed nanobodies exert an antiviral effect during BVDV infection and whether they can be used for BVD treatment were not clear.…”
Section: Discussionmentioning
confidence: 99%